„W tym szaleństwie jest metoda”, czyli do czego Freudowi potrzebny był Hamlet? .......... 165 - Marciniak-Pinel , Magdalena (Na Przełomie: 25 lat seminarium filozoficznego. Uniwersytet Jagielloński 1995-2020, 2020)
“THOUGH THIS BE MADNESS, YET THERE IS METHOD IN IT”, OR WHY FREUD NEEDED HAMLET?Freud sees Oedipus as a universal figure of repressed fantasy and he is wondering if he can be founded in Hamlet. Freud suggests a new reading of Shakespeare’s Hamlet, different from Goethe’s and Coleridge’s analyses. According to them, Hamlet was an un-emblematic figure of psychological weakness who didn’t have the strength to revenge for his father’s death. The novelty of Freud’s reading was to stress the importance of Hamlet’s internal conflicts. Onto Freudian’s stage enters a new protagonist: the unconscious.